(untitled) (London Journal of Engineering Research, 2024)
Many literature reviews dealt with the effect of fibers on concrete performance by using different types of fibers. This study introduces some literatures related to using fibers in reinforced concrete beams for the period (2004-2021). The following section presents the previous studies of the flexural behavior of fiber reinforced concrete (FRC) beams for steel type of fiber especially. Next, the points of agreement and disagreements between studies are demonstrated briefly. Moreover, comments on previous studies are inserted. Then, a section covers the benefits of previous studies. Finally, the knowledge gap is clarified by recognizing this study’s differences.